PENGARUH TIPE KEPEMILIKAN TERHADAP PERFORMA CORPORATE SOCIAL RESPONSIBILITY PERUSAHAAN NON KEUANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Alvine Adriyadi; Basuki Hadiprajitno (Diponegoro Journal of Accounting, 2015)
This study aims to examine the effect of ownership type and corporate social responsibility of firm. The purpose of this study is to provide empirically evidence about the effect of ownership type to corporate social responsibility of firm. The independent variables of this study are ownership type by financial institution, government, corporate investor, and individual investors, the dependent variable is CSR, and control variables are size and profitability. CSR measured by CSR disclosure with GRI G3.1 as the indicator. Ownership type measured by disclosure showed in annual report. Size measured by logarithm of total asset. Leverage measured by total debt to total equity, and ROA measured by total profit to assets.The population in this study are 507companies which listed on Indonesian Stock Exchange in the period of 2013. Sample were selected by purposive sampling method and finally obtained 225 companies that fulfill the criteria. Data were analyzed using multiple regression analysis model.The result show that ownership by government significantly positive to CSR. Based on the result, conclude that ownership by government will take action of responsibility besides making profit from the firm.